2012
DOI: 10.1039/c2cc30981e
|View full text |Cite
|
Sign up to set email alerts
|

Highly reactive meso-like positions of dipyrihexaphyrin

Abstract: The meso-like position of a pyridine-containing porphyrin analogue structurally related to amethyrin was found to be highly reactive to undergo addition of alcohols, amines and hydrogen cyanide at room temperature under neutral conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Pyridine-modified rubyrin 6 underwent protonation-induced flipping of the pyridine subunits 17 , and cyclo [6]pyridine [6]pyrrole 7 was synthesized as the largest pyridine-incorporating expanded porphyrin that showed characteristic conformational flexibility (Fig. 1) [14][15][16][17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…Pyridine-modified rubyrin 6 underwent protonation-induced flipping of the pyridine subunits 17 , and cyclo [6]pyridine [6]pyrrole 7 was synthesized as the largest pyridine-incorporating expanded porphyrin that showed characteristic conformational flexibility (Fig. 1) [14][15][16][17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…A recent example by Osuka and co-workers demonstrated that water can insert into the meso -position of hexaphyrin (1.1.1.1.1.1) upon Cu( ii )- or Ni( ii )-metallation 32. Setsune and co-workers have also reported that dipyriamethyrin can undergo meso -selective nucleophilic addition with cyanide, amines, and alkoxides 33. Elegant demonstrations of ring contraction have been observed by the Furuta group with N -confused dihydrosapphyrin to give neo -confused corrole,34 as well as by Maruyama, Fujita, Osuka, and co-workers with bis-Cu( ii )octaphyrin to give Cu( ii )-porphyrin 35.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several pyridyl derivatives have been reported, including pyriporphyrin ( 2 ) and its Zn II ( 2 a ) and Fe III complexes, confused pyriporphyrin and its Fe II , Fe III , and Pd II complexes, oxypyriporphyin and its Ni II[6e] and Fe III[6f] complexes, and a dipyridinoid‐substituted porphyrin derivative. Similarly, a variety of pyridine‐based derivatives have been described and characterized: (i) expanded porphyrins, such as 12‐hydroxypyrisapphyrin, dipyrihexaphyrin, tetrapyrioctaphyrin, bipyrioctaphyrin, and cyclo[ m ]pyridine[ n ]pyrroles; (ii) phathalocyanine derivatives such as hemiporphyrazines; (iii) calixpyrrole derivatives such as meso ‐octaethyl calix[4]pyridine; and (iv) cryptand‐like pyriporphyrinoid macrocycles . Recently, a series of porphyrin‐related macrocycles with N4 coordination spheres were reported, including: 1,10‐phenanthroline‐embedded porphyrins ( 3 ) as Mg II sensors; carbazole and pyridine building blocks with high‐spin Co II complexes; and cobalt(II) phenanthroline‐indole macrocycles as electrocatalysts for oxygen reduction .…”
Section: Figurementioning
confidence: 99%